ANALISIS SISTEM AKUNTANSI TERHADAP PENCATATAN PELAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) DI KABUPATEN KAPUAS HULU (Studi Kasus Pada Badan Kepegawaian Daerah) - B51112004, PAULUS ARDIGO PALKALSE (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Government institutions is a working unit or organizational unit ministries or departments, non-departmental government agencies, kesekretariat higher institutions of State, and other government institutions, both national and local. Drafting local development planning document is the implementation of the mandate of Law Number 32 Year 2004 on Regional Government, with memperhatiakan Law Number 17 Year 2003 on State Finance and Law No. 25 of 2004 on the national development planning system. In compiling RKPD (local government work plan), the main reference used is the direction and program with establishment of the area as outlined in the document Development Plan (medium term development plan) area then be adjusted to the conditions and characteristics of the problems of the local area as well as a variety of program development priorities. In addition, RKPD (local government work plan) in the formulation also refer to the documents the work plan Regional device unit (SKPD Renja). The research objective was to determine whether the Regional Employment Board of Kapuas Hulu has done the accounting records properly (according to Government Regulation No. 71 Year 2010 Article 1 paragraph (3) of government accounting standards) as a reference. as well as to know the constraints faced by the Agency for Regional personnel in conducting financial recording and reporting. In analyzing the data collected authors use qualitative methods in order to understand the data obtained in the form of records and financial statements and the Regional Employment Board verifies the theory through evidence. Agency staffing area. The results of this study menunjukkaan agency staffing area Kapuas Hulu in financial management have not been fully able to realize financial management which includes aspects of accountability, integrated between the stages of budgeting, penatausaha and accountability, as mandated by the Minister Regulation No. 71 of 2010 on Guidelines for Financial Management Area. Keywords: analysis, recording, reporting.